2020
DOI: 10.1021/acs.est.0c02363
|View full text |Cite
|
Sign up to set email alerts
|

Combined Biotic–Abiotic 2,4-Dinitroanisole Degradation in the Presence of Hexahydro-1,3,5-trinitro-1,3,5-triazine

Abstract: The Department of Defense has developed new explosive formulations in which traditionally used cyclic nitramines such as hexahydro-1,3,5-trinitro-1,3,5-triazine (RDX) have been updated with the insensitive munition (IM) 2,4-dinitroanisole (DNAN). Understanding combined degradation of both compounds at explosive-contaminated sites will allow remediation approaches that simultaneously target both contaminants. DNAN reduction in the presence of RDX was evaluated in abiotic experiments using substoichiometric, sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Although microbial community analyses could not be conducted in this study to determine specific microbes involved in the degradation reactions, WBC-2 characterization has shown a wide variety of microorganisms (Jones et al, 2006;Lorah et al, 2008a;Molenda et al, 2016). Microbial groups in WBC-2; span many of the groups identified as containing RDX-degraders, including Pseudomonas, Clostridia, and Geobacteraceae (Kwon and Finneran, 2006;Cho et al, 2013Cho et al, , 2015Cho et al, , 2016Wang et al, 2017;Niedźwiecka et al, 2020). Another study showed that anaerobic cultures developed to degrade chlorinated ethenes (predominantly trichloroethene), similar to WBC-2, could also degrade RDX (Young et al, 2006).…”
Section: Implications For Bioremediationmentioning
confidence: 99%
“…Although microbial community analyses could not be conducted in this study to determine specific microbes involved in the degradation reactions, WBC-2 characterization has shown a wide variety of microorganisms (Jones et al, 2006;Lorah et al, 2008a;Molenda et al, 2016). Microbial groups in WBC-2; span many of the groups identified as containing RDX-degraders, including Pseudomonas, Clostridia, and Geobacteraceae (Kwon and Finneran, 2006;Cho et al, 2013Cho et al, , 2015Cho et al, , 2016Wang et al, 2017;Niedźwiecka et al, 2020). Another study showed that anaerobic cultures developed to degrade chlorinated ethenes (predominantly trichloroethene), similar to WBC-2, could also degrade RDX (Young et al, 2006).…”
Section: Implications For Bioremediationmentioning
confidence: 99%
“…30,63 Additionally, the microbial nitroaromatic compound reduction using synthetic quinones as electron shuttles has also been demonstrated. 22,23 However, to the best of our knowledge, this is the first study showing that the regeneration of the quinone moieties of NOM via chemical reactions with nitroaromatic compounds allows the cells to produce energy, even when only very low concentrations of quinones are present. By demonstrating the cycle using real humic acids, the results also validate previous studies that applied AQDS as an electron shuttle.…”
Section: Resultsmentioning
confidence: 92%
“…NOM components such as ESHA, PPHA, Leonardite humic acid, and Suwannee River humic and fulvic acids have been previously shown to be possible final electron acceptors for anaerobic microbial respiration. , Additionally, the microbial nitroaromatic compound reduction using synthetic quinones as electron shuttles has also been demonstrated. , However, to the best of our knowledge, this is the first study showing that the regeneration of the quinone moieties of NOM via chemical reactions with nitroaromatic compounds allows the cells to produce energy, even when only very low concentrations of quinones are present. By demonstrating the cycle using real humic acids, the results also validate previous studies that applied AQDS as an electron shuttle. , Furthermore, the process was studied for a culture composed mostly of Geobacter , a model soil microorganism, and using NOM, which is ubiquitous in many environmental matrices. Thus, the results have important implications on the mechanisms by which microbes can obtain energy from the reduction of nitroaromatic contaminants in nature and establish that the nitroaromatic reduction can occur wherever NOM respiration exists.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations